Higher Education in Albania: The Never Ending Challenge - Kajsiu, Blendi (International Higher Education, 2015)
During the last twenty-five years the growing demand for higher education in Albania has not been met by a proportional growth in funding for the sector. So far the challenge of accommodating a growing demand for higher education in the context of limited financial resources has produced three different reforms of the higher education sector. Their common denominator has been the unwillingness or the inability of different governments to provide funding that matches the growing demand. This is why the challenge of higher education in Albania still remains intact.